The structural model of the effects of psychological strain, defeat, and thwarted belongingness on suicidal ideation in adolescents via the mediation of depression and hopelessness - Moosivand, Mahboobeh; Bagian Kulemarzi, Mohammad Javad; Zaremohzzabieh, Zeinab; Zarean, Mansoureh; Rajabi, Moslem; Khanjani, Sajad (Routledge, 2024)
Objective: This study aimed to identify factors associated with suicidal ideation (SI) in adolescents and to explore the mediating role of depression and hopelessness in these predictive relationships. Method: Employing a cross-sectional research design, this study included adolescents aged 14 to 19 from Lorestan Province in Iran. A total of 623 middle-school students were selected through a multi-stage cluster sampling technique. Data were collected using a series of assessment tools, including the Depressive Symptom Index- Suicidality Subscale (DSI-SS), the Psychological Strain Questionnaire, the Hopelessness Scale, the Defeat Scale, and the Thwarted Belongingness Questionnaire. Structural Equation Modeling (SEM) in AMOS version 26 and SPSS version 26 was utilized to evaluate the proposed model. Results: The findings revealed that in the context of Iranian adolescents, defeat and psychological strains emerge as significant predictors of SI. Notably, hopelessness was found to mediate the relationship between psychological strains, defeat, and SI. Conclusion: These insights provide valuable knowledge for addressing the issue of SI in Iranian adolescents and may inform future prevention and intervention strategies.